miR‐181a overexpression predicts the poor treatment response and early‐progression of serous ovarian cancer patients - Panoutsopoulou, Konstantina; Avgeris, Margaritis; Magkou, Paraskevi; Mavridis, Konstantinos; Dreyer, Tobias; Dorn, Julia; Obermayr, Eva; Reinthaller, Alexander; Michaelidou, Kleita; Mahner, Sven; Vergote, Ignace; Loverix, Liselore; et al. (International Journal of Cancer, 2020)
Ovarian cancer (OC) remains a leading cause of gynecological cancer‐related death worldwide, characterized by poor 5‐year survival. Molecular markers could serve as crucial tools of personalized prognosis and therapy. Herein, we present miR‐181a as novel predictor of OC prognosis, using five independent OC cohorts. In particular, a screening (n = 81) and an institutionally independent validation (n = 100, OVCAD multicenter study) serous OC (SOC) cohorts were analyzed. Bagnoli et al (2016) OC179 (n = 124) to OC133 (n = 100) and TCGA (n = 489) served as external validation cohorts. Patients’ survival and disease progression were assessed as clinical endpoint events. Bootstrap analysis was performed for internal validation and decision curve analysis was utilized to evaluate clinical benefit. miR‐181a overexpression was unveiled as powerful and independent molecular predictor of patients’ poor survival and higher risk for disease progression after debulking surgery and platinum‐based chemotherapy. Analysis of the OVCAD institutionally independent cohort, as well as of Bagnoli et al. and TCGA external cohorts further confirmed the unfavorable prognostic nature of miR‐181a overexpression in SOC. Strikingly, multivariate prognostic models incorporating miR‐181a with established disease markers clearly improved patients’ risk‐stratification and offered superior clinical benefit in OC prognostication. Conclusively, miR‐181a evaluation could augment prognostic accuracy and support precision medicine decisions in OC. What's new? Ovarian cancer remains difficult to treat and has a low 5‐year survival rate. Biological markers associated with the disease could help develop personalized therapy or refine prognosis. The microRNA miR‐181a has been shown to mediate EMT transition and inhibit apoptosis. Here, the authors looked for miR‐181a in five independent cohorts of ovarian cancer patients. They found that miR‐181a overexpression predicted poor survival and increased risk of disease progression. Testing for this marker could improve the way that patients’ risk is assessed and help guide treatment decisions.